Właściwości odpadów na hałdach górniczych węgla kamiennego w Nowej Rudzie w aspekcie ich biologicznej rekultywacji = Properties of waste rock deposited on mine spoils of hard coal mines in Nowa Ruda with the perspective of their biological reclamation - Szopka, Katarzyna; Bogda, Adam; Karczewska, Anna; Gałka, Bernard; Wojtkowiak, Marta; Pruchniewicz, Daniel (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Examined were the properties of unburned waste rock on the mine spoil of the coal mine Piast in Nowa Ruda. Waste material was relatively ho-mogeneous in various parts of the spoil. It contained high amounts of skeleton and residual coal, and its pH was neutral or alkaline. The salinity was in the class 0, and Pb, Zn, and Cu concentrations were low. Those properties should not negatively affect the process of reclamation.
Keywords: hałdy; węgiel kamienny; gleba; rekultywacja; mine spoils; soils; reclamation; hard coal mining